Ethnoscience Study of Rangrang Woven Fabric from Seraya Karangasem as Supporting Material for Junior High School Science Education - Ni Putu Dhita Prahita Prameswari; Kompyang Selamet; Putu Hari Sudewa (Jurnal Pijar MIPA, 2026)
The importance of linking science education to the local cultural context so that scientific concepts become more meaningful to students. This study aims to examine the potential of ethnoscience in the traditional rangrang woven fabric of Seraya, Karangasem, as a supplement to junior high school science curriculum. The study employs a descriptive qualitative research design using an ethnoscience approach. The research subjects included business owners, two weavers in Seraya Village, and three science teachers at SMP Negeri 3 Amlapura, selected through purposive sampling. Data were collected through observation, semi-structured interviews, and questionnaires, and analyzed using the Miles and Huberman model across the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the process of making rangrang woven fabric incorporates various scientific concepts, including the classification and transformation of materials in the use of natural dyes (indigo, noni, and others) and the process of spinning cotton into thread, the principles of simple machines in the use of traditional tools, concepts of heat and its transfer during the boiling process, pH concepts in the dyeing and color-fixing processes, as well as concepts of force, motion, and work in weaving activities. The conclusion of this study indicates that the entire process of making rangrang woven fabric is closely connected to the junior high school science curriculum and has the potential to serve as a contextual learning resource grounded in local wisdom. This integration of ethoscience can help students understand scientific concepts more tangibly while fostering awareness of cultural and environmental preservation.